A Development Of An Internet Of Things Equipped Unmanned Ground Vehicle For Surveilance Purpose - Azizan, Anis Natasha (Universiti Sains Malaysia, 2019)
An Unmanned Ground Vehicle (UGV) is a ground vehicle that operates remotely, without having human on-board. UGVs are widely used for mission-based applications that are often hazardous or inconvenient for humankind. Practically, depending on its purposes, UGVs often equipped with sensors and on-board camera to enable self-navigation in order to achieve the desired mission requisite. the number of devices involved in machine-to-machine communications is expected to steadily grow, thus realizing the envisioned revolution called the Internet of Things (IoT), in which one of the main proclaimed goal is to connect everything and everyone everywhere to everything and everyone else. In this project, the UGV combines two main elements, which are collision avoidance system (CAS), path planning system (PPS) and implementation of (IoT) for data analysing in developing an IoT equipped UGV for surveillance purpose. Costing is highly concerned for this project, therefore a low-cost ultrasonic sensor (HC-SR04) is used as a distance sensor for obstacle detection and avoidance purpose. Meanwhile, an Arduino Mega 2560 (Controller) is used as microcontroller for obstacle avoidance and path optimization purpose respectively. The maneuver is assisted with ultrasonic sensors (front and rear) sense and avoid the obstacles within 1 to 2 meters range. The ultrasonic sensors are programmed in such a way that it sweeps the sensors that the field of view of 180° angle both front and rear of the vehicle. Path planning is the key element for unmanned vehicle. Therefore, controller is used for navigation before and after approaching obstacles. Path planning algorithm in this project provides the best path to avoid the obstacle and create temporary new waypoints within split seconds. This practice makes the UGV more authentic and proximately imitable with human sensors and its responses. The second element, implementation of IoT is with the purpose of collecting surveillance data. The data will be sent into the cloud with the assist of Wi-Fi module NodeMCU so it can be connected to the internet. The data stored in the cloud can be retrieved and processed using ThingSpeak software as this software allow user to aggregate, visualize, and analyze live data streams in the cloud. These implementations possibly makes the UGV more authentic and widen its application in mission-based operation or even in simple commercial operation.